RESPON UJI TERHADAP SUSU KAMBING PERANAKAN ETAWAH YANG DISIMPAN PADA SUHU RUANG - Nugroho J.,N.P; N.P. Mariani; I.A. Okarini (Jurnal Peternakan Tropika, 2019)
Milk has high nutrition, this causes milk to be a medium that is very favored by microorganisms for their growth and development. Damage that occurs in milk results in a decrease of it quality that can be known by test of it. This study aims to determine the fat content, alcohol test, LAB and flavor of milk during storage of room temperature. Milk samples were obtained from Etawah Crossbreed (PE) dairy goat farms in Sepang Village, Busung Biu District, Buleleng Regency. This research was conducted for 1 month from 29 June - 2 August 2018. The design used was a Completely Randomized Design (CRD), with 3 storage treatments at room temperature namely P0 (0 hour of storage), P4 (4 hours of storage) and P6( 6 hours of storage) repeated 4 times, so the samples examined were 12 samples. The variables observed in this study were alcohol test, fat content, amount of LAB and flavor. The data obtained were analyzed with variance, if there were significant differences (P<0.05) then the analysis continued with Duncan's multiple range test. The results showed that the alcohol test at P0 and P4were negative results, while on P6was a positive result. Fat content of P4 (86.04%) and P6 (49.35%) and P4 BAL (44.5%) increased significantly (P<0.05) compared to P0. P4 taste (17.14%) and P6 (35.71%) significantly decreased (P<0.05) compared to P0 with the longer storage time. Based on the results of the study it can be concluded that the goat milk stored for 4 hours at room temperature was the best treatment in maintaining milk freshness in terms of alcohol test, fat content, total LAB and flavor preferences. Keywords: Goat milk, storage, alcohol test, LAB, fat content, flavor